Divergence and Convergence in the Governance of European Higher Education - Shattock, Michael (International Higher Education, 2025)
<h3 id="the-lisbon-declaration-established-the-concept-of-european-universities-being-at-the-heart-of-the-knowledge-economy-and-encouraged-a-modernization-of-european-systems-the-bologna-process-and-the-horizon-europe-program-represent-important-outcomes-less-attention-has-been-given-to-the-modernization-of-higher-education-systems-and-the-alignment-of-the-granting-of-university-titles-european-systems-are-largely-diverging-rather-than-converging-undermining-the-benefits-of-convergence-in-teaching-arrangements-and-research-and-conflicting-with-the-concept-of-a-european-higher-education-area" data-pm-slice="1 1 []">The Lisbon Declaration established the concept of European universities being at the heart of the knowledge economy and encouraged a modernization of European systems. The Bologna Process and the Horizon Europe program represent important outcomes. Less attention has been given to the modernization of higher education systems and the alignment of the granting of university titles. European systems are largely diverging rather than converging, undermining the benefits of convergence in teaching arrangements and research and conflicting with the concept of a European Higher Education Area.